The peruvian genome project: expanding the global pool of genome diversity from South America - Guio, Heinner; Sanchez, Cesar; Borda, Victor; Jaramillo-Valverde, Luis; Caceres, Omar; Padilla, Carlos; Trujillo, Omar; Poterico, Julio A.; Silva-Carvalho, Carolina; Horton, Mary; Lanata, Cristina M.; Carnevale, Alessandra; et al. (Frontiers in Genetics, 2025)
The process of inhabiting the Americas by ancestral native American populations involved many individuals settling in the Peruvian Andes and Amazonian regions. Due to Latin American countries representing less than 1% of the human genome data available in public reference databases, the evolution and migration processes involved in adapting have not yet been fully explained. The Peruvian Genome Project is an initiative, started in 2011, to address the genomic data underrepresentation from native South American populations. This project has collected 1,149 samples from 17 traditional native and 13 mestizo (mixed of native, African, and European ancestry) communities. Currently, 150 whole genomes and 873 array-genotyped individuals have been analyzed including coastal, Andes, and Amazonian regions. We discovered 1.6 million novel genetic variants with varying frequencies, indicative of local environmental adaptations and genetic drift. These novel variants allow us to infer adaptive traits and population-specific allele frequencies for people living at different altitudes and varying adaptations to pathogens or living conditions. The Peruvian Genome Project is the result of over a decade of work in sample selection, logistics, and approved regulatory community engagement, designed to enhance the human genome pool of native Americans diversity. The data collected here enable the targeted characterization of endemic diseases, trait adaptations, and new clinical significance variants in South America. The Peruvian Genome Project represents a step forward in international and multidisciplinary efforts to make precision medicine more inclusive and accessible for underrepresented communities in Latin America, offering significant potential for drug development and diagnostics in a neglected continent.